Kajian Kesiapan Dokumen Akreditasi Kelompok Kerja Administrasi Manajemen di Upt.Puskesmas Jelbuk Dinas Kesehatan Kabupaten Jember (Study of Preparation on Accreditation Document for Administration Management at Jelbuk Primary Health Center Jember) - Agus Sulistinah; Eri Witcahyo; Cristyana Sandra (Pustaka Kesehatan, 2017)
In order to perform the functions, the primary health center should be a good governance system. Primary Health Center management system includes management of service performance, service process, and resources used. Communities require safe and quality health services and can answer their needs, therefore quality improvement, risk management and patient safety also need to be applied in the management of primary health center in providing comprehensive health services to the community. It can be done by accreditation assessment The purpose of this study is to describe the readiness of accreditation documents of administrative and management working groups in UPT. Public Health Center Jelbuk Jember. This type of research was qualitative research. The results of the research at Public Health Center Jelbuk from the completeness of the document that was done by using the check list of completeness available 72 documents from 84 documents required 85,7% so that Public Health Center Jelbuk included assesment criteria that is document completeness> 80%. Primary Health Center Should be prepared in the assessment of accreditation will be planning for July 2017Keywords: Primary Health Center, accreditation, preparation, administratiton, management.